Crisis? What crisis? Football in Germany - Frick, B.; Prinz, J. (Journal of Sports Economics, 2006)
The purpose of this article is to describe the financial situation and the development of club finances of the German "Bundesliga". Using data provided by the football association and data collected from a number of different sources we find that the majority of the teams are economically well established: Revenues have increased steadily, liabilities are under control, and player salaries have considerably declined. The ongoing debate about the liabilities of the German soccer teams is clearly misleading because two largemarket teams are principally responsible for the overall increase of the clubs' liabilities.